Primary pure squamous cell carcinoma of the gall bladder – a case report of rare and aggressive entity with adverse prognosis - Bargotya, Mona; Mehta, Ankita; Das, Payel; Sachan, Ashish (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The most common malignancy of the biliary tract is gall bladder carcinoma and the main subtype according to the histological classification is Adenocarcinoma. Pure squamous cell carcinoma of the gall bladder is very rare entity accounting for only 1.1-3.7% of the gall bladder carcinomas. It is highly malignant with poor prognosis due to high proliferative rate and local invasiveness to the adjacent organs. The patients are usually diagnosed at an advanced stage with a bulky tumor owing to its aggressive behavior. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. In this paper, we describe a female patient with primary pure squamous cell carcinoma of the gall bladder. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 42-year old female patient presented with chief complaints of pain in abdomen associated with nausea and vomiting and gradually progressive jaundice since 02 months. Contrast Enhancing Computed Tomography (CECT) abdomen showed an enhancing mass lesion in gall bladder involving adjacent organs for which she underwent extended cholecystectomy with pancreaticoduodenectomy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Diagnosis as well as the management of this exceptionally rare type of tumour is undoubtedly challenging because of non-specific clinical as well as imaging findings. This case report is an attempt to add to the literary evidence for better pathological as well as clinical understanding of this rare and aggressive entity thereby providing additional material for the early diagnosis as well as the development of effective targeted therapies which will certainly help in increasing the lifespan of these patients.